Application of the debris-flow hazard index for pipelines in the context of the hydrogeological disaster of February 2023 in São Sebastião, Serra do Mar, Brazil - Veloso, Vinicius Queiroz [UNESP]; Reis, Fabio Augusto Vieira Gomes [UNESP]; Cabral, Victor [UNESP]; Sá, Artur A.; Gramani, Marcelo Fischer; Ribeiro, Thiago Castro [UNESP]; Ogura, Agostinho Tadashi; do Santos Corrêa, Claudia Vanessa [UNESP]; Mascarenhas, Pedro Victor Serra; Russo, Wanderley; Sánchez, Joana Paula [UNESP]; Kuhn, Caiubi Emanuel Souza; et al. (Springer Nature, 2025)
Debris flows are a type of natural disaster that poses great threat to infrastructure, humans and the environment. In Brazil, debris flows have caused significant damage, especially in the Serra do Mar Mountain region. The increasing frequency and intensity of extreme precipitation events in the country highlights the need for the development of effective landslide risk management strategies. In this study, we analyze the initiation and dynamics of a debris-flow event that occurred in the Toque-Toque Grande watershed based on numerical modeling, as well as the risk that debris-flow occurrences represent to pipeline crossings using the Debris-flow Hazard Index methodology. The Toque-Toque Grande watershed is located in São Sebastião, northern coast of the São Paulo state (Brazil), where in February 18–19, 2023, an unprecedent precipitation event triggered landslides and debris flows. The results revealed that the intensification of extreme precipitation frequency and volume over short periods demands a more in-depth analysis. Instantaneous events, occurring without prior accumulations, are becoming increasingly frequent. It becomes imperative to urgently comprehend their dynamics and their relationship with natural disasters, especially debris flows, and their impact on urban centers and strategic infrastructures along impact routes. The increasing frequency and intensity of extreme precipitation events highlight the need for adaptable risk management strategies focused on prevention to mitigate impacts on infrastructure, society, and the environment. Additionally, the study emphasizes the urgency of structural protection measures following the magnitude of the 2023 event, evidenced by meteorological and geomorphological assessments, highlighting the influence of physical environmental conditions on the formation of debris flows. Computational modeling aided in visualizing the dynamics of the flow, providing crucial understanding for its dynamics. The identification of high-risk areas and the implementation of containment measures, exemplified by the protection structure of Transpetro in the Toque-Toque Grande basin, highlight the importance of proactive structural measures in impact mitigation. Essentially, this study sought to demonstrate the complexity of debris flow risk management, advocating for multidisciplinary approaches, prevention strategies, emergency response, and infrastructure protection in the face of environmental and operational challenges.
Keywords: Debris flow; Environmental risk management; Geomorphological influences; Hazard assessment; Infrastructure resilience; Multidisciplinary approaches